Bacterial and fungal influence on the mineralization of bovine manure: evidence on soil fertility in the cultivation of quinoa (Chenopodium quinoa Willd.) - Paco Perez, Víctor (2022)
Organic residues in soil are often degraded by the dynamic action of soil life. The objective of the present study was to determine the bacterial and fungal influence on the mineralization of bovine manure (BM) in soil. The research was carried out at the Centro Experimental Agropecuario de Condoriri, Oruro, Bolivia, at an altitude of 3,830 m asl. BM was applied to the pots at concentrations of 0.9, 1.9, 3.3, 4.2, 5.0, 5.6 and 6.7%, which were homogenized with river sand separately. 5 to 10 seeds of C. quinoa were manually sown in the pots. Soil samples were collected from the pots for microbiological analysis every 30 days, while macronutrients were collected at the end of plant physiological maturity. Bacteria were evaluated in Plate Count Agar (PCA) culture of 10-5 dilutions and fungi in Potato Dextrose Agar (PDA) of 10-2 solutions. The results indicate that alkaline pH does not reduce the population of bacteria and fungi. It was found that, at higher microbial population, nitrogen (N) has higher mineralization than other essential minerals. On the other hand, it was observed that the higher the degree of application of BM and the higher the soil moisture concentration, the more favorable the effects on the increase of bacterial and fungal populations. It is concluded that BM mineralization depends on high concentrations of bacterial and fungal populations as well as on soil moisture.